PENGARUH MANAJEMEN LABA, FINANCIAL DISTRESS, KINERJA KEUANGAN, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN - Ameera, Nadya; Rahardjo, Shiddiq Nur (Diponegoro Journal of Accounting, 2021)
This study aims to analyze and obtain empirical evidence of the effect of earnings management, financial distress, financial performance, leverage and firm size on firm value. The sample in this study was selected using a purposive sampling method totaling 41 manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. The method of analysis used in this research is multiple linear regression.Based on the research conducted, it is found that earnings management has a negative and significant effect on firm value. The financial distress variable that measured using the Altman Z-score has a positive and significant effect on firm value. Then for financial performance measured using Basic Earning Power(BEP) has no effect on firm value while leverage has a positive and significant effect on firm value. Other results concluded that firm size has no effect on firm value.